Pattern and Outcome of Paediatric Non-Communicable Diseases in a Teaching Hospital in Southern Nigeria - Atimati, Anthony O.; Eyo-Ita, Emmanuel; Eki-Udoko, Fidelis E. (International Journal of Child Health and Nutrition, 2023)
Non-communicable diseases (NCDs) are chronic non-transmissible diseases that are mainly attributable to lifestyle changes. There is a global increase in this category of diseases, which in developing countries constitute an added burden to the already existing burden of communicable diseases. This study aims at determining the prevalence, pattern, length of hospital stay and outcome of children admitted with non-communicable diseases. Methods: This is a retrospective cross-sectional study carried out in the paediatric wards of our hospital. Data was extracted from records of children admitted within the study period. The data was analyzed using the Statistical Package for Social Sciences (IBM SPSS) version 23. The student t-test was used to compare the means between two groups, while an ANOVA was used for more than two groups. Result: Out of 820 children studied, 32.2% had NCDs with sickle cell disease, neoplasms, and cardiovascular and neurological diseases, constituting the major non-communicable diseases recorded. There was a significantly longer duration of hospital stay and a higher mortality rate in patients admitted with an NCD. There was a significant association between mortality and the category of NCD, with a greater contribution from neoplastic diseases. Conclusion: There is a high prevalence of paediatric non-communicable diseases, although communicable diseases are still more prevalent among children in this study. This is associated with poor outcomes and a longer duration of hospital stay.